Humanistic Counseling Values in the Qur'an: A Tafsir Analysis of Surah Ali 'Imran Verse 159 on the Principle of Gentleness: Nilai-Nilai Konseling Humanistik dalam Al-Qur'an: Analisis Tafsir Surah Ali Imran Ayat 159 tentang Sikap Lemah Lembut - Rahmi Umaira Rahmi (Ikhtisar: Jurnal Pengetahuan Islam, 2026)
This research is motivated by the importance of applying the values of humanistic communication and counseling in social life, which currently tends to experience a crisis of empathy, a harsh attitude in communicating, and a decline in gentleness in human interaction. The Qur'an, as a guide to life, provides principles of humanistic communication, one of which is found in Surah Ali Imran verse 159. This study aims to analyze the values of humanistic counseling contained in the interpretation of Surah Ali Imran verse 159 and its relevance in the practice of Islamic communication and counseling. This study uses a qualitative research method with a library research approach. The main sources of data come from the Qur'an, the tafsir of Ibn Katsir, as well as the scientific literature related to humanistic communication and Islamic counseling. The data analysis technique is carried out through a descriptive-analytical method by examining the meaning of the verse based on the interpretation of the mufassir. The results of the study show that Surah Ali Imran verse 159 contains humanistic counseling values in the form of a gentle attitude, empathy, forgiveness, deliberation, and respect for individuals. These values form a fundamental base for developing communication which is not only effective and harmonious but also humanitarian in its approach, according to Islam. In addition, this particular verse acts as a guide to humanistic communication and counseling across various social and educational settings.